3PC-016 Vancomycin eye drops at 50 mg/mL: physicochemical stability, impact of packaging and storage conditions. (23rd March 2022) - Gouverneur, B; Gouverneur, B; Roche, M; Berneron, C; Margolle, A; Creton, L; Nassar, C; Lannoy, D; Odou, P
Abstract : Background and importance: Vancomycin eyedrops (VED) are unavailable in Europe and are usually compounded as extemporaneous in hospital pharmacies. Aim and objectives: To collect data on VED physicochemical stability in three different containers stored either refrigerated or frozen. Material and methods: VED at 50 mg/ml (10 mL) were aseptically compounded under a laminar flow hood from injectable vancomycin and sterile water for injection (Baxter) and stored in amber glass (n=26; Gravis), classical (n=26; CAT) or innovative Novelia (n=26; Nemera) low-density polyethylene (LDPE) bottles. Assays were performed according to GERPAC-SFPC stability studies guidelines on vials stored either at 2–8°C (analysis at days D1-D3-D7-D15-D40-D60-D90) or frozen at –20°C for 60 days, then thawed (room temperature (RT) or 2–8°C) and refrigerated once thawed (post-thaw analysis at D1-D3-D7-D20). At each time point in the study vancomycin concentration (using a stability-indicating HPLC-UV method), pH and osmolality were determined, and the visual aspect was checked. Sterility and non-visible particle count (by light obscuration particle count test) were performed at the beginning and end of the study. Non-parametric tests were used to compare containers and storage conditions (α=5%). Results: Vancomycin concentration (mean ± standard deviation; expressed as a percentage of the initial value) when stored at 2–8°C from D1 to D60 was between 95.7±1.6% and 107.4±2.1% (except at D7, due to material bias) and 89.5±1.6% and 92.8±1.9% at D90. Vancomycin concentration in vials thawed at RT or 2–8°C was, respectively, between 95.8±1.1% and 102.2±4.3% and 95.3±2.3% and 101.1±4.1% at D7 and between 89.3±1.8% and 93.9±0.6% and 89.9±0.8% and 92.7±1.2% at D20 after thawing. No significant difference was found between packaging (p=0.323) or thawing method (p=0.736). pH and osmolality, respectively, 3.31±0.06 and 46.12±3.61 mOsm/kg, remained stable with no difference between containers (p=0.242 and p=0.414) or thawing methods (p=0.287 and p=0.999). A slight yellow colouration of VED (2–8°C) was perceived after D60. A slight increase in non-visible particles count was observed between D1 and D90 in glass and classic LDPE but values complied with the European Pharmacopoeia 2.9.19 threshold. Conclusion and relevance: VED remained stable for 2 months refrigerated or frozen, and for 7 days after thawing (RT or 2–8°C). These results will allow the preparation of a stock of VED that is available immediately. A microbiological stability study in real conditions of use should complete this work. References and/or acknowledgements: Conflict of interest: No conflict of interest